Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

Étude sur les besoins spécifiques des femmes immigrantes francophones en situation minoritaire - Alliance des femmes de la francophonie canadienne (L’Alliance des femmes de la francophonie canadienne (AFFC), 2021)

Stratégies d’intégration et de support en santé mentale des immigrants francophones au Canada anglais. - Archambault, Hélène; de Moissac, Daniel; Tempier, Raymond (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Cet article explore les stratégies d’intégration au système de santé telles que proposées par des personnes immigrantes francophones au sein de communautés francophones en situation minoritaire au Canada (CFSM). Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante personnes adultes immigrantes ou réfugiées. Centrées sur les représentations des personnes immigrantes quant aux services de soutien en santé mentale, diverses stratégies ont été dégagées. La préparation prémigratoire et le regroupement des informations sous un guichet unique semblent contribuer à une intégration réussie. L’appui des organismes communautaires et des autorités religieuses est bénéfique pour le soutien informationnel et socioémotionnel des nouveaux arrivants, ayant des retombées positives sur leur bien-être et leur capacité de s’intégrer à leur nouveau milieu de vie. Mots-clés : immigration, francophones, intégration, système de santé, stratégies Abstract This article explores healthcare integration strategies proposed by Francophone immigrants within Francophone minority communities (FMCs) in Canada. A qualitative study using semi-structured interviews was conducted in three Canadian cities with sixty adult immigrants and refugees. Focusing on immigrants’ perceptions of mental health support services, various strategies were identified. Pre-migration preparation and centralizing information seem to contribute to successful integration. The support of community organizations and religious authorities is beneficial for the socio-emotional and information support of newcomers, having a positive impact on their well-being and their ability to integrate into their new living environment. Keywords: immigration, Francophones, integration, healthcare, strategies

New Brunswick's elders neglected and forgotten - Association francophone des aînés du Nouveau-Brunswick (Comité d'action sur la bienveillance envers les personnes aînées, 2022)

Vieillir dans l'indifférence et l'indignité au Nouveau-Brunswick - Association francophone des aînés du Nouveau-Brunswick (Comité d'action sur la bienveillance envers les personnes aînées, 2022)

Des nôtres (Volet 2): Expériences des jeunes 2ELGBTQ+ en milieu scolaire, familiale et communautaire vivant en situation linguistique minoritaire dans la province du Manitoba. - Avanthay-Strus, Jacqueline; de Moissac, Danielle; Gueye, Ndeye Rokhaya; Sandoval, Lyle-Alvien; Girard, Rhéanne; Gagné, Daniel; Costeux, Anne-Lise; Franco Morales, Freddy; Le groupe Jeunes chercheur.es; Le collectif LGBTQ* du Manitoba (Le Collectif LGBTQ du Manitoba et Université de Saint-Boniface, 2024)
Les populations ayant des identités intersectionnelles comme les jeunes 2ELGBTQ* francophones en situation linguistique minoritaire au Canada, peuvent faire face à diverses formes de discrimination dans leur vie quotidienne. Cette discrimination peut provenir de plusieurs sphères, y compris sociale, économique et institutionnelle, et elle peut entraîner des conséquences graves sur la santé mentale et physique des individus. Les études ont montré que lorsque cette discrimination est combinée au stress lié au fait d’appartenir à une minorité linguistique ou culturelle, cela peut amplifier les iniquités sociales et celles liées à la santé. Cela peut se traduire par des difficultés d’accès aux services de santé adaptés, par des taux plus élevés de dépression, d’anxiété et d’autres problèmes de santé mentale, ainsi que par des obstacles à l’inclusion sociale et économique. Une approche de recherche-action participative (RAP) a été privilégiée pour cette étude. Cette méthode efficace et inclusive a permis de faire participer étroitement les membres de la communauté au processus de recherche. Les adolescent·es et jeunes adultes francophones 2ELGBTQ* ont joué un rôle clé, non seulement en partageant leurs expériences, mais aussi en collaborant activement à la création du devis de recherche. Un devis mixte (quantitatif et qualitatif) à convergence des données a été adopté pour explorer les expériences de vie des jeunes 2ELGBTQ* d’expression française en situation linguistique minoritaire au Manitoba, dans leur milieu scolaire, familial et communautaire, ainsi qu’avec les services sociaux et de santé. Huit jeunes entre 14 et 24 ans ont participé à des entrevues progressives. Le sondage en ligne a été fait auprès de 45 jeunes de 14 à 24 ans. Six parents de jeunes 2ELGBTQ* ont participé à un entretien individuel ou à des entretiens en groupe, et quatre membres du personnel des écoles ont participé à une discussion en groupe. Trois quarts des jeunes qui ont répondu au sondage habitaient en milieu urbain. À peu près un quart d’entre eux sont des personnes autochtones, noires ou de couleur (PANDC), et trois quarts disent être bilingues (français et anglais). La grande majorité a indiqué avoir un trouble de santé mentale. Plus de la moitié a signalé une absence de réseaux de soutien en français pour les personnes 2ELGBTQ*. Un pourcentage élevé a signalé avoir des difficultés à tisser des liens ou à se faire des ami·es lors des interactions à l’école. Une difficulté à trouver des espaces surs, que ce soit en ligne ou en personne, a aussi été mentionnée. Le constat selon lequel un pourcentage élevé a signalé des difficultés à tisser des liens ou à se faire des ami·es lors des interactions à l’école indique un besoin d’amélioration des environnements éducatifs. Il est essentiel que le personnel des écoles et les autres élèves soient sensibilisés et formés pour créer des espaces surs et accueillants pour toutes les identités 2ELGBTQ* francophones. Les résultats soulignent l’urgence de mettre en place des mesures concrètes pour favoriser l’inclusion, offrir un soutien adéquat et créer des espaces sécuritaires et inclusifs pour les personnes 2ELGBTQ* francophones. Cela peut passer par des initiatives de sensibilisation, des programmes de soutien psychosocial, des ressources éducatives et des politiques visant à promouvoir la diversité et l’inclusion au sein des écoles et des communautés francophones. Les recommandations s’adressent donc aux milieux éducatifs, aux systèmes sociaux et de santé ainsi qu’à la communauté.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Distance, access and equity: A cross-sectional geospatial analysis of disparities in acess to primary care for French-only speakers in Ottawa, Ontario - Belanger, Christopher; Carr, Kady; Peixoto, Cayden; Bjerre, Lise M. (CMAJ Open, 2023)
Background: Although language concordance between patients and primary care physicians results in better quality of care and health outcomes, little research has explored inequities in travel burden to access primary care people of linguistic minority groups in Canada. We sought to investigate the travel burden of language-concordant primary care among people who speak French but not English (French-only speakers) and the general public in Ottawa, Ontario, and any inequities in access across language groups and neighbourhood ruralities. Methods: Using a novel computational method, we estimated travel burden to language-concordant primary care for the general population and French-only speakers in Ottawa. We used language and population data from Statistics Canada’s 2016 Census, neighbourhood demographics from the Ottawa Neighbourhood Study, and collected the main practice location and language of primary care physicians from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Results: We included data from 869 primary care physicians and 916 855 patients. Overall, French-only speakers faced greater travel burdens than the general population to access language-concordant primary care. Median differences in travel burden were statistically significant but small (median difference in drive time 0.61 min, p < 0.001, interquartile range 0.26–1.17 min), but inequities in travel burden between groups were larger among people living in rural neighbourhoods.

Étude sur les populations âgées et l’accès aux soins de longue durée en français en Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)
Ce rapport présente une analyse de la demande et de l’offre de services de santé en français (SSF) dans le secteur des soins de longue durée (SLD) en Ontario. En nous appuyant sur des données publiques ainsi que sur des données administratives fournies par le ministère de la Santé de l’Ontario, le rapport examine : 1. la demande régionale de SSF, évaluée selon la population ontarienne âgée de 65 ans et plus et la population francophone de ce groupe d’âge ; 2. l’offre de SSF, mesurée par le nombre et le type de foyers présents dans chaque région, ainsi que par les compétences linguistiques en français de leur personnel.

Study of aging populations and access to French-language long-term care in Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)

Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 21 : ConnectAînés / Francsavoir (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

Pratique # 22 : Bien vieillir chez soi / Soutien à domicile (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

La santé en contexte francophone minoritaire au Canada : 20 ans de recherche: Introduction - Bouchard, Louise; Savard, Jacinthe; Dumond, Morgan (Minorités linguistiques et société, 2024)

État des connaissances sur la santé et les services de santé aux aînés francophones en contexte linguistique minoritaire - Bouchard, Louise; Savard, Jacinthe; Renaud, Alexandre (Reflets, 2022)
La recherche en santé sur les communautés de langue officielle en situation minoritaire (CLOSM) a connu un essor remarquable ces deux dernières décennies. L’objectif de cet article est de présenter un état des lieux de la recherche effectuée sur la problématique de la santé et des soins destinés aux personnes âgées francophones en situation linguistique minoritaire. Différents thèmes sont abordés tels que la santé et ses déterminants, l’expérience des usagers quant à la langue des services, l’environnement légal et politique des services en français, l’organisation des services et la performance du système de santé. Cette synthèse évaluative de la recherche vise à fournir un outil de mobilisation des connaissances et des pistes d’action pour mieux répondre aux besoins des populations aînées et pour améliorer l’offre de services. Mots-clés : revue de littérature, aînés francophones, santé, services et politiques de santé, minorité de langue officielle, Canada

L'offre active de services de santé mentale en français en Ontario et au Manitoba : les rôles clés des instruments et des outils - Cardinal, Linda; de Moissac, Danielle; Deschênes-Thériault, Guillaume (Administration publique du Canada / Canadian Public Administration, 2023)
Cet article présente les données d'un sondage réalisé en 2019 sur la connaissance des gestionnaires et des professionnels œuvrant dans le domaine de la santé mentale en Ontario et au Manitoba de leurs obligations linguistiques et des outils qui favorisent la pratique de l'offre active de services français. L'étude permet de souligner que plus les professionnels et les gestionnaires comprennent leurs obligations, tant en Ontario qu'au Manitoba, plus ils peuvent profiter des outils existants pour s'en acquitter. L'étude montre qu'il existe en effet un lien entre la connaissance des obligations et l'utilisation des outils pour faire de l'offre active de services de santé mentale en français. Elle permet aussi d'insister sur le rôle clé des outils pour faire de l'offre active de services en français.

Évaluer le potentiel de soins linguistiquement concordants pour les francophones de l’Ontario : une étude populationnelle transversale. - Carr, Kady; Batista Moliner, Ricardo; Fitzgerald, Michael; Lamontagne, Sophie; Bader Eddeen, Anan; Timony, Patrick E.; Bédard, Daniel; Gauthier, Alain; Prud’homme, Denis; Landry, Josette-Renée; Chomienne, Marie-Hélène; Denis-Leblanc, Manon; et al. (Minorités linguistiques et société, 2024)
Cette étude a utilisé les données sur les médecins, la facturation et le recensement de 2016 dont dispose l’ICES pour examiner l’accès potentiel à des médecins de famille francophones pour les francophones résidant dans 1 643 aires de diffusion agrégées (ADA) de l’Ontario. L’Ontario compte 550 280 francophones, soit 4,1 % de sa population. Nous avons identifié 8 199 médecins de famille, parmi lesquels 1 169 se sont autodéclarés francophones. Le ratio provincial global pour les francophones était de 2,12 médecins par 1 000 résidentes et résidents, comparativement à un ratio de 0,66 pour les anglophones. Dans les ADA où les francophones étaient majoritaires, le ratio pour les francophones était inférieur au ratio pour les anglophones (0,63 vs 2,02), alors que dans toutes les autres ADA, le ratio francophone était plus élevé (3,46 vs 0,62 dans les 83,4 % des ADA où les francophones représentaient >0 % à <5 % de la population). Huit ADA du Nord-Est et de l’Est de l’Ontario présentaient un déficit relatif important de médecins de famille francophones par rapport au ratio provincial. Ces résultats donnent un aperçu des régions qui pourraient bénéficier de programmes visant à éliminer les barrières linguistiques. Mots-clés : Concordance linguistique, médecins de famille, accès aux soins primaires, francophones, Ontario

Plaidoyer pour la santé - Un guide pratique - Chaput, Sarah (Réseau francophone international pour la promotion de la santé, 2022)

Le moment Monfort dans la francophonie canadienne. - Charbonneau, François (Presses de l’Université d’Ottawa, 2024)

Perceptions des professionnels de la santé quant aux besoins oncologiques pédiatriques offerts en français à domicile : étude descriptive qualitative - Chartrand, Julie; Jibb, Lindsay; Grandmont, Camille; Hardy-Bélanger, Élisabeth; Cheng, Sara; Balasa, Rebecca; Johnston, Donna (Revue canadienne de soins infirmers en oncologie, 2022)

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Améliorer les services et les soins offerts aux communautés francophones en situation minoritaire au Canada : entre recherche, dialogue et formation. - Collin, Stéphanie; Bouchard, Pier; Vézina, Sylvain; Cormier, Manon (Minorités linguistiques et société, 2024)
Au regard de l’amélioration des services et soins de santé offerts aux communautés francophones en situation minoritaire (CFSM), la programmation du Groupe de recherche et d’innovation sur l’organisation des services de santé (GRIOSS) de l’Université de Moncton a constamment évolué. Depuis 2009, les travaux de l’équipe de recherche ont été névralgiques, développant une compréhension plus fine de divers enjeux « évolutifs du terrain » s’inscrivant dans des thèmes généraux comme la gestion et l’organisation des services et soins de santé ainsi que la gouvernance. Cet article présente, sous forme d’un récit historique, l’évolution de la programmation de recherche du GRIOSS et une synthèse des résultats de recherche ainsi que des extrants ayant influencé la pratique. Un élément central du bilan : les savoirs issus de ces recherches ont servi, au fil du temps, à nourrir la réflexion commune et le dialogue s’est traduit par des changements sociaux durables au sein des CFSM. Mots-clés : communautés francophones en situation minoritaire, accès aux services de santé dans la langue officielle de son choix, offre active, recherche-action, dialogue

Accès aux services de santé en français et gouverne en réseau : différentes représentations et stratégies d'action - Collin, Stéphanie; Grenier, Gabrielle; McIntyre, Martine; Roy, Shanie (Revue Gouvernance, 2022)
Au Canada, l’enjeu de l’amélioration de l’accès aux services de santé en français, surtout dans les provinces hors Québec, s’inscrit dans des relations complexes entre différents acteurs qui poursuivent des objectifs variés. En 2008, au Nouveau-Brunswick, l’État a remplacé les huit régies régionales existantes par deux nouvelles régies, soit la Régie régionale de la santé A (Réseau de santé Vitalité) et la Régie régionale de la santé B (Réseau de santé Horizon). Plus tard, il a été établi que Vitalité fonctionnerait en français et Horizon en anglais, et que les réseaux assureraient la prestation des services de santé dans la langue officielle du choix des citoyens. Ainsi, l’objectif général de la recherche était de comprendre l’influence des dynamiques entre les acteurs d’une gouverne en réseau sur le traitement de l’enjeu que représente l’accès aux services de santé en français. Une méthode qualitative comprenant notamment des entretiens semi-directifs (n=26) a été retenue. Les résultats montrent que, d’une part, l’offre de services dans la langue du choix des citoyens, qui est conditionnée par le cadre juridique sur les droits linguistiques, pousse les acteurs à mobiliser des stratégies axées sur la qualité et la sécurité. D’autre part, l’accès révèle une dimension symbolique, puisqu’il est associé aux notions d’équité et de gouvernance. L’accès aux services de santé en français est un sujet délicat pour l’État, qui demeure en retrait par rapport à celui-ci. Afin de mieux répondre aux besoins en santé des citoyens, cet acteur doit faire émerger des liens de confiance et formuler des objectifs clairs. Mots-clés : gouverne, réseau, accès, santé, communautés francophones en situation minoritaire, langues officielles

La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

Coup d’œil sur la recherche : Qualité et sécurité des soins de longue durée en Ontario [infographie] - Consortium national de formation en santé; van Kemenade, Solange (2022)

Bien dans notre peau: Élaboration d’un outil de diagnostic pour informer la conception et l’évaluation de services et partenariats sécuritaires, inclusifs et équitables pour toute personne 2ELGBTQ+ d’expression française au Manitoba - Courcelles, Rémi; Hardy, Stephan; Prada, Kevin (Santé Canada, 2023)

Les Petits et les Grands amis : Faciliter des échanges et développer des attitudes favorables entre les générations en milieu minoritaire. - de Moissac, Danielle; Arbez, Dominique; Alper, David; Bourrier, Patricia (Université de Saint-Boniface, 2021)
Dans la francophonie canadienne en contexte minoritaire, la population croissante d’aînés est à risque d’isolement social en raison des effets du vieillissement et du statut linguistique minoritaire. Les aînés vivant avec la démence sont davantage vulnérables à l’isolement, ce qui peut avoir comme conséquence d’aggraver le déclin cognitif et psychologique. D’autre part, la mobilité familiale, en particulier celle des familles immigrantes, fait en sorte que les échanges entre générations sont moins fréquents, tant pour les enfants que pour les aînés. Ce manque d’exposition et d’échanges entre les générations peut avoir un effet sur les enfants et mener à une perception défavorable des personnes âgées. Des études ont démontré que la participation aux programmes intergénérationnels favorise la santé physique et mentale des aînés, ainsi que leur engagement social. Pour les enfants, ces programmes favorisent leurs compétences sociales et émotionnelles et le développement d’attitudes positives à l’égard des aînés. Les programmes visant les aînés avec la démence et les enfants d’âge préscolaire suggèrent une attention particulière aux choix d’activités pour maintenir l’intérêt des deux groupes tout en respectant leurs capacités physiques et cognitives. Un programme intergénérationnel a été mis en place pour pallier l’isolement social des aînés et favoriser le développement d’attitudes positives chez les enfants à l’égard des aînés tout en reflétant la langue et les diverses cultures de la francophonie manitobaine. Une étude a été menée, ayant comme objectifs d’examiner l’impact de cette initiative sur le sentiment d’isolement social des résidents aînés d’un foyer de soins de longue durée et la perception des enfants quant aux aînés. Un programme intergénérationnel comprenant 8 séances d’activités a eu lieu à l’automne 20 9 au foyer de soins de longue durée dans un espace permettant aux enfants et aux aînés de participer à des activités de grand rassemblement et des activités en petits groupes. Les enfants du service de garde éducatif se déplaçaient une fois par semaine pour y participer. Des entrevues semidirigées ont été effectuées avant et après le programme intergénérationnel auprès ) des enfants, pour qualifier leur perception des personnes âgées et 2) auprès des aînés, en ce qui a trait à leur réseau social et leur sentiment d’isolement. De plus, les parents/ tuteurs des enfants participants ont été invités à compléter un questionnaire sur l’expérience de leur enfant auprès des personnes âgées avant les sessions intergénérationnelles. Les enfants participants ont pu créer des dessins commentés représentant leurs expériences avec les aînés à la suite de leur participation aux sessions intergénérationnelles. De plus, des observations ont été faites par des assistants de recherche lors des séances d’activité. Quelques membres du personnel du foyer de soins de longue durée et du service de garde éducatif ont également rempli un questionnaire d’évaluation de l’activité intergénérationnelle. Ainsi, l’ensemble des perspectives nous a permis de mieux saisir les effets des échanges intergénérationnels sur les participants.

Mental health status and help-seeking strategies of international students in Canada - de Moissac, Danielle; Graham, Jan Marie; Prada, Kevin; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Canadian Journal of Higher Education, 2020)
International students are at heightened risk of developing psychological distress, yet little research has been conducted on their mental health or support needs. This quantitative study focused on undergraduate students at two mid-sized universities in Manitoba, Canada. Online and paper surveys were completed by 932 participants, of whom 21% identified as international students. This paper, descriptive in nature, outlines the sociodemographic profiles, current mental health status, psychological characteristics, and coping strategies of international students compared to domestic students in each institution. Data show that international students are more likely to report excellent mental health, score higher on the mental health scale, and report higher life satisfaction, higher self-esteem, and more positive body image than domestic respondents. However, they are less likely to talk about their hardships. Providing culturally-adapted supports that take into consideration ethnolinguistic differences, religious practice, and mental health literacy will better meet the needs of international students on campus.

Healthcare Service Utilization and Perceived Gaps: The Experience of French-Speaking 2S/LGBTQI+ People in Manitoba - de Moissac, Danielle; Prada, Kevin; Gueye, Ndeye Rokhaya; Avanthay-Strus, Jacqueline; Hardy, Stephan (Healthcare Policy, 2024)
Ethnolinguistically diverse 2S/LGBTQI+ (two-spirit, lesbian, gay, bisexual, transgender, queer and intersex) populations have unique healthcare needs and experience health inequities compared to their cisgender or heterosexual peers. This community-based participatory study sought to describe the profile and healthcare needs and experiences of official language minority French-speaking 2S/LGBTQI+ adults in Manitoba. Participants (N = 80) reported that gender and sexual identity were often concealed from service providers; many respondents faced discrimination based on their ethnolinguistic and sexual identities. Service gaps are identified pertaining to mental and sexual health; locating 2S/LGBTQI+-friendly, patient-centred care in French is difficult. Policy and practice should address systemic inequity and discrimination experienced by this equity-seeking population.

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

Accès aux services en santé dans la langue officielle de leur choix par les minorités francophones hors Québec. Analyse de données secondaires - Diaz Pinsent Mercier Research Inc (Consortium national de formation en santé, 2021)

Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Vers une amélioration de la prestation de services de santé pour les Franco-Ontariens - Doucet, Pascale-Anne. M.; Gorham, Robyn; Hunt, Elena (Journal de recherche interdisciplinaire, 2021)
Malgré le statut de dualité linguistique du Canada, la communauté francophone continue d’être laissée pour compte par les autorités du pays. Plus spécifiquement, l’étendue et l’accès restreints des services de santé offerts aux francophones en Ontario posent un grave danger pour cette population. Les établissements qui dispensent des services de santé continuent d’ignorer les politiques de soins existantes. Cette situation impose plusieurs actions au niveau fédéral, législatif et communautaire nécessaires afin d’assurer la garantie bilingue promise à la population canadienne. Parmi celles-ci, il faut augmenter la présence francophone dans les groupes décisionnels pour assurer la conception et l’établissement de programmes et services de santé axés sur les besoins uniques et distincts des franco-ontariens. Par ailleurs, l’engagement financier fédéral envers des organismes communautaires francophones est essentiel afin de fournir plus de services de santé en français, surtout dans les communautés nordiques et rurales de la province. Finalement, la subvention gouvernementale de futures recherches sur la santé des francophones est nécessaire puisque celles-ci vont servir de base solide pour déterminer comment mieux desservir cette population. Pour y arriver, il faudrait considérer le lobbying, l’encouragement des institutions qui dispensent des services de santé d’obtenir leur désignation bilingue, et la mise à jour de la Loi sur les services en français. Cependant, en continuant l’inaction, les Franco-Ontariens risquent de devenir assimilés au restant de la population, de dépérir et de voir leur santé se détériorer. Cet article cherche notamment à signaler la nécessité d’améliorer la prestation de services de santé en français en Ontario.

Soins à domicile et soins palliatifs communautaires. Synthèse et analyse des services, des besoins et des pratiques exemplaires ou innovantes dans les communautés francophones en situation minoritaire (CFSM). Rapport de recherche. Consortium national de formation en santé. - Dupuis-Blanchard, Suzanne (Consortium national de formation en santé, 2022)

Soins et services pour le maintien à domicile des personnes aînées des communautés francophones en situation minoritaire. - Dupuis-Blanchard, Suzanne (Minorités linguistiques et société, 2024)
L’accès aux soins et aux services à domicile en français pour les personnes aînées des communautés francophones en situation minoritaire (CFSM) représente un défi pour le maintien à domicile. Le but de cet article est de présenter le contexte dans lequel baignent les soins et les services à domicile, de résumer l’état des connaissances sur le sujet basé sur les travaux de l’autrice, et d’offrir un aperçu de l’avenir des soins et services à domicile. Les résultats de cette synthèse de la littérature démontrent qu’il y a très peu d’écrits portant sur le maintien à domicile en CFSM alors que les personnes aînées francophones sont plus âgées que leurs homologues anglophones. Par conséquent, les travaux de l’autrice permettent d’établir une base sur laquelle de futures initiatives peuvent s’ancrer. Quant à l’avenir des soins et services à domicile, certaines perspectives permettent d’émettre quelques idées pour l’avancement des connaissances dans le domaine. Mots-clés : vieillissement, domicile, CFSM, autonomie, services

Naviguer le maintien à domicile en communautés de langue officielle en situation minoritaire rurales : enjeux et pistes de solutions - Dupuis-Blanchard, Suzanne; Caissie, Julie (Reflets, 2021)
Le vieillissement de la population dans les provinces de l’Atlantique est une réalité courante en plus d’une composition géographique rurale et la présence de communautés de langue officielle en situation minoritaire (CLOSM). Les objectifs de cette étude descriptive qualitative étaient de 1) comprendre les services utilisés pour le maintien à domicile, et 2) déterminer les services nécessitant une amélioration pour l’accès en français. Vingt-six (n=26) personnes âgées ont participé à cette étude en région rurale de l’île du Prince Édouard. Les résultats témoignent des difficultés d’accès aux services pour le maintien à domicile tout en offrant des pistes de solutions pour l’améliorer. Mots-clés : Maintien à domicile, vieillissement, communautés de langue officielle en situation minoritaire, communauté rurale, services, recherche qualitative

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Regards sur la société canadienne, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Insights on Canadian Society, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Creating a Culture of Active Offer in Both Official Languages: A Case Study of a Dialogue - Forgues, Éric; Paulin, Christine C. (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Abstract To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles. Keywords: health in French, service language, active offer, organizational culture, linguistic skills of organizations Résumé Afin d’implanter une culture de l’offre active (OA) des services dans les deux langues officielles, le réseau de santé Horizon au Nouveau-Brunswick a mené des sessions de dialogues auprès de plus de 3 400 employés. Ces dialogues ont permis aux participantes et aux participants d’exprimer leurs opinions sur l’OA, les défis rencontrés et des pistes de solution. Notre projet visait à mieux comprendre la portée des activités de dialogue sur le développement d’une culture de l’OA au sein du réseau de santé Horizon. L’analyse des évaluations réalisées après chacune des sessions, de la documentation interne et des entretiens menés auprès de huit organisatrices et animatrices de ces dialogues, montre que ce type d’exercice recèle un potentiel pour mettre en place une culture de l’OA, tout en permettant de mieux comprendre certains blocages. Mots-clés : santé en français, langue de service, offre active, culture organisationnelle, compétences linguistiques des organisations

Vers une culture de l’offre active de services de santé dans les deux langues officielles, étude de cas d’une pratique de dialogue. - Forgues, Éric; Paulin, Christine C. (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Afin d’implanter une culture de l’offre active (OA) des services dans les deux langues officielles, le réseau de santé Horizon au Nouveau-Brunswick a mené des sessions de dialogues auprès de plus de 3 400 employés. Ces dialogues ont permis aux participantes et aux participants d’exprimer leurs opinions sur l’OA, les défis rencontrés et des pistes de solution. Notre projet visait à mieux comprendre la portée des activités de dialogue sur le développement d’une culture de l’OA au sein du réseau de santé Horizon. L’analyse des évaluations réalisées après chacune des sessions, de la documentation interne et des entretiens menés auprès de huit organisatrices et animatrices de ces dialogues, montre que ce type d’exercice recèle un potentiel pour mettre en place une culture de l’OA, tout en permettant de mieux comprendre certains blocages. Mots-clés : santé en français, langue de service, offre active, culture organisationnelle, compétences linguistiques des organisations Abstract To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles. Keywords: health in French, service language, active offer, organizational culture, linguistic skills of organizations

Understanding acceptability of digital health technologies among francophone-speaking communities across the world: a meta-ethnographic study - Gauthier-Beaupré, Amelie; Grosjean, Sylvie (Frontiers in Communication, 2023)
Introduction: Increasingly, people are turning toward digital health technologies to support their care management, communication with health professionals, and performing activities of daily living. Digital health technologies may be well implemented in clinical practices in several jurisdictions, but the influence of sociocultural factors may sometimes be neglected. To increase use and sustainability of these innovative solutions in health care, we need to understand acceptability among diverse groups of the population such as linguistically diverse populations. Francophone-speaking populations in Canada, for example, are known to endure challenges with income, health and difficulties associated with living in rural areas which impede on their likelihood to use digital health technologies. As part of the University of Ottawa International Francophonie Research Chair on Digital Health Technologies, this study aimed to understand the conditions that make digital health technologies acceptable among francophone-speaking communities. Methods: Using a meta-ethnography methodology, this study synthesizes international qualitative research on social acceptability of digital health technology among francophone-speaking communities. We focused on four types of digital health technologies: telemedicine, mobile technologies, wearable technologies, and robotic technologies. Using Noblit and Hare's 7 phase approach to conducting a meta-ethnography, we were able to get a comprehensive synthesis and understanding of the research landscape on the issue. Studies published between 2010 and 2020 were included and synthesized using NVivo, excel and a mind mapping technique. Results: Our coding revealed that factors of social acceptability for digital health technologies could be grouped into the following categories: care organization, self-care support, communication with care team, relational and technical risks, organizational factors, social and ethical values. Our paper discusses the themes evoked in each category and their relevance for the included digital health technologies. Discussion: In discussing the results, we present commonalities and differences in the social acceptability factors of the different digital health technologies. In addition, we demonstrate the importance of considering sociocultural diversity in the study of social acceptability for digital health technologies. Implications: The results of this study have implications for practitioners who are the instigators of digital health technology implementation with healthcare service users. By understanding factors of social acceptability among francophone-speaking communities, practitioners will be better suited to propose and support the implementation of technologies in ways that are suitable for these individuals. For policymakers, this knowledge could be used for developing policy actions based on consideration for diversity.

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Amy. T.; Ménard, Alixe; Scott, Mary (Université d'Ottawa et Institut de recherche Bruyère, 2022)

Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Hsu, Amy; Ménard, Alixe; Scott, Mary (Bruyère Research Institut, 2022)

Practice #28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)

Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Recueil des outils proposés dans le guide pratique Plaidoyer pour la santé - Knaidil, Ibtissam; Chaput, Sarah (Réseau francophone international pour la promotion de la santé, 2022)

La première étape de la validation transculturelle des versions anglophones des tests de l'horloge et du Mini-Mental pour mesurer les capacités cognitives des Franco-Ontariens âgés de plus de 65 ans - Larocque, Sylvie; Lavoie, Anne-Marise; Omri, Nadia (Reflets, 2021)
La maladie d’Alzheimer est un syndrome neurodégénératif chronique caractérisé par un déclin cognitif et mnésique. Les personnes atteintes par cette maladie développent des affections rattachées à la langue. Il est important de faire passer des tests de dépistage dans la langue maternelle de la personne puisque l’aptitude linguistique décline avec la progression de la maladie. De manière générale, le Mini-mental et le test de l’horloge sont administrés en anglais aux francophones du nord de l’Ontario ce qui peut mener à une sous-évaluation de leurs capacités cognitives et à un diagnostic erroné. Voilà pourquoi le but de cette recherche était de développer et valider les tests psychométriques francophones administrés aux Franco-Ontariens. Le Mini-mental et le test de l’horloge ont été traduits selon la validation transculturelle de Caron (1999) et testés auprès des francophones du Grand Sudbury qui souffraient de déficits cognitifs (N=14). Aucune différence statistique (p>.05) entre les scores de la traduction franco-ontarienne du test de l’horloge et du Mini-mental comparés aux tests originaux n’a été détectée. Bien que d’autres recherches soient nécessaires, selon les auteures, ces traductions permettront d’assurer un dépistage juste de cette maladie chez les francophones âgés en situation minoritaire. Mots-clés : dépistage d’Alzheimer, Mini-mental de Folstein, test de l’horloge, traduction transculturelle

Exploring Primary Care Physicians’ Experiences of Language and Cultural Discordant Care for Linguistic Minority Patients at the End-of-Life: A Study Protocol - Lee, Seung Heyck; Gibb, Maya; Karunananthan, Sathya; Cody, Margaret; Tanuseputro, Peter; Johnston, Sharon; Kendall, Claire; Bedard, Daniel; Collin, Stéphanie; Kehoe MacLeod, Krystal (International Journal of Qualitative Methods, 2023)
Health disparities exist across different linguistic groups. Language barriers in primary care can negatively affect access to healthcare services and the quality and safety of care at the end-of-life. This study will take a novel, in-depth look at the experience of language- and/or cultural-discordant care for adults from linguistic minority groups through the eyes of primary care physicians providing palliative and/or end-of-life care. Language and cultural discordance means that the physician and patient do not speak the same language or are not from the same cultural background. Qualitative data from primary care physicians (n = 12–24) providing language-discordant end-of-life care to Francophone and/or Allophone older adults across different care models and diverse geographies in Ontario will be collected through semi-structured interviews. Reflexive thematic analysis will be used to report themes within the data and consider the influence of the social locations of the researcher and research participants, geographic considerations impacting service provision, and barriers imposed by differing primary care funding structures on the provision of palliative and end-of-life care for linguistic and cultural minority groups in Ontario. Findings from this study will identify the interconnections among language and cultural discordance, care model, geographic region, and physician perceptions of their combined effects on access to, and quality of, palliative and end-of-life care. This evidence will be key to informing clinical practice guidelines and mobilizing change to improve primary care access and quality for adults at the end-of-life from linguistic and cultural minority populations across Ontario. Keywords: language discordance, qualitative research, reflexive thematic analysis, palliative care, primary care physicians, semi-structured interviews

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)

Validation culturelle d’un outil numérique francophone pour l’histoire médicale en soins de santé primaires - McGraw, Monica; Dionne Merlin, Marjolaine; Dion, Cynthia; Renaud, Julie; Légère, Danika; Poirier, Marie-Dominique (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
La technologie de santé numérique s’intègre dans les soins de santé améliorant l’engagement des patients dans les décisions partagées, favorisant ainsi leur prise en charge et la qualité des soins. FirstHx développe des outils innovants dans cette optique, mais leur mise en oeuvre est complexe pour la population francophone dans un contexte majoritairement anglophone. Cette étude vise à valider culturellement cet outil et à évaluer la satisfaction des utilisateurs. Une méthodologie mixte séquentielle explicative est employée en trois phases : un sondage quantitatif pour tester la clarté des questions, des entretiens semi-dirigés pour explorer la traduction culturelle et la convivialité, et une validation par des experts via la méthode Delphi. L’outil validé optimisera les pratiques cliniques, normalisera la saisie des données d’anamnèse et ouvrira de nouvelles perspectives de recherche. Cette validation offrira à la population francophone un accès équitable à des outils numériques innovants, renforçant leur engagement dans leurs soins. Digital health technology is being integrated into healthcare, improving patient engagement in shared decision-making, thereby promoting their care and the quality of care. FirstHx develops innovative tools with this goal in mind, but their implementation is complex for the Francophone population in a predominantly English-speaking context. This study aims to culturally validate this tool and assess user satisfaction. A sequential explanatory mixed-method approach is used in three phases: a quantitative survey to test question clarity, semi-structured interviews to explore cultural translation and user-friendliness, and validation by experts using the Delphi method. The validated tool will optimize clinical practices, standardize the collection of medical history data, and open new research opportunities. This validation will provide the Francophone population with equitable access to innovative digital tools, strengthening their engagement in their healthcare.

Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Ménard, Alixe; Scott, Mary; Hsu, Amy T. (2022)

Accès aux soins de longue durée dans la région d'Érié St. clair : Analyse et recommandation - Mian, Guy (Entité de planification des services de santé en français Érié St.Clair/Sud-Ouest, 2021)
Ce rapport a été préparé dans le cadre du Plan d’Action Conjoint 2019-2022 du RLISS-Entité,¹ où les soins et les services aux aînés sont considérés comme prioritaires et, en particulier, l’accès aux soins de longue durée (SLD) dans la région d’Érié St. Clair. Le présent rapport vise à formuler des recommandations à l’intention de Santé Ontario (SO) Ouest afin de combler les lacunes en matière d’accessibilité aux soins de longue durée (SLD) en français et, par conséquent, dans les services de soutien à domicile et en milieu communautaires (SSDMC) afin de maintenir les aînés francophones à domicile dans la région d’Érié St. Clair (ESC). Dans la mesure du possible, le rapport proposera également des recommandations pour la localité de London dans la région du Sud-Ouest (S-O).

Pratique # 20 : Talking About Mental Illness (TAMI) en français (Territoires du Nord-Ouest) - Michel, Jean Nephetaly; van Kemenade, Solange; Benoît, Josée (2021)

Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and their Nursing Care Providers - Muray, Mwali (2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system. Keywords: Francophonie, Linguistic Minorities, Nursing, Phenomenology, Qualitative Research

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

The revised patient perception of patient-centeredness questionnaire: Exploring the factor structure in French-speaking patients with multimorbidity - Nguyen, Tu Ngoc; Ngangue, Patrice Alain; Ryan, Bridget. L.; Stewart, Moira; Brown, Judith. B.; Bouhali, Tarek; Fortin, Martin (Health Expectations, 2020)
Background The Patient Perception of Patient-Centeredness (PPPC) questionnaire was revised, and there is a need for the questionnaire to be tested in diverse primary care populations. Objectives This study aimed to examine the factor structure of the Revised PPPC questionnaire (PPPC-R) in French-speaking patients with multimorbidity. Design Secondary analysis from baseline data of the French arm of Patient-Centered Innovations for Persons with Multimorbidity Study (PACEinMM Study). Setting and participants Participants were adult patients with multimorbidity attending primary health-care settings. Outcome measures Exploratory factor analyses were applied to examine the factor structure of the PPPC-R. Cronbach's alpha values were calculated to assess the internal consistency of the whole questionnaire and of each factor explored. Results There were 301 participants, mean age 61.0, 53.2% female. The PPPC-R showed very good internal consistency, with three factors: Patient-Centered Clinical Method (PCCM) Component 1-Exploring the health, disease and illness experience + PCCM Component 4-Enhancing the patient–clinician relationship (Factor 1); PCCM Component 2-Understanding the whole person (Factor 2); and PCCM Component 3-Finding common ground (Factor 3). There was a good internal consistency within each factor (Cronbach's α = 0.87 for 8 items in Factor 1, 0.77 for 5 items in Factor 2 and 0.87 for 5 items in Factor 3). Discussion and conclusions The French PPPC-R factor structure was in accordance with the underpinning conceptual model and presented with three factors. Further assessment of its validity and reproducibility are needed to allow its use as a measure of patient's perception of patient-centeredness.

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Le programme de télésanté de prévention des chutes Marche vers le Futur : développement et retombées d’une communauté de pratique franco-canadienne - O’Neil, Jennifer; Dionne, Nathalie; Cardinal, Dominique; Savard, Jacinthe (Minorités linguistiques et société, 2025)
Résumé Le programme de télésanté Marche Vers le Futur (MVF) a eu un impact positif sur le bien-être des personnes âgées francophones et sur leur accès aux services de prévention des chutes au Canada. L’objectif de ce projet était de développer et de mettre en place une communauté de pratique (CdP) facilitant le partenariat et le partage des connaissances entre les animateurs du programme MVF. La création de cette CdP a permis à vingt-deux animateurs de cinq provinces de partager des stratégies de recrutement, de promotion du programme et de sensibilisation quant aux besoins des personnes âgées francophones au pays. Quatre rencontres virtuelles ont permis d’identifier les obstacles à la pérennité de MFV, les facteurs facilitant la mobilisation des connaissances ainsi que les initiatives de formation continue. La CdP a permis de renforcer les réseaux de partenariat entre les chercheurs et les animateurs du programme MVF, ce qui pourrait avoir un impact important sur l’équité en santé chez les personnes âgées francophones vivant en situation minoritaire au Canada. Abstract Marche vers le Futur (MVF) is a telehealth program that has demonstrated a positive impact on the access to fall prevention services in Canada and the wellness of older Francophone adults living in minority situations. This project aimed to develop and implement a community of practice (CoP) to facilitate partnership and knowledge-sharing between MVF program facilitators across francophone communities in Canada. The creation of this CoP enabled twenty-two facilitators from five provinces to share strategies for recruiting, promoting, and sustaining the program as well as continuing to raise awareness around the importance of health prevention services tailored for older Francophone adults in Canada. Four virtual meetings were held to identify sustainability barriers, knowledge mobilisation facilitators, and continuing education initiatives. The CoP allowed to strengthen the partnership between researchers and program facilitators across diverse provinces which could impact health equity among older Francophone adults living in minority communities in Canada.

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

Francophone patients - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Patientèle francophone - Patrie, Mélanie; Barbeau-Rodrigue, Danielle; Morris, Vanessa (Canadian Medical Association Journal, 2024)

Substance Use, Addiction and Support Services: Increased Risk and Service Inequity for Official Language Minority Communities in Canada - Prada, Kevin; de Moissac, Danielle (The Canadian Journal of Addiction, 2024)
Abstract Objectives: The increase in substance use and addictions within the Canadian population, illustrated by the current opioid crisis and exacerbated by the COVID-19 pandemic, urges the investigation of populations who may be particularly vulnerable to developing problematic substance use. Official language minority communities in Canada, both understudied and underserved, may be one such population. Methods: Through its tripartite design using scoping literature review, interview, and environmental scan methodologies, this study offers a snapshot of the current reality surrounding substance use, addictions, and related treatment services available to this linguistic minority population. Results: Results reveal significant gaps in knowledge and service provision for this population. Service provision and knowledge on this issue constitute a nationwide patchwork, leaving official language minority communities underserved. While enough is known to assert that their needs are different than those of their majority peers, much remains to be investigated, and efforts to ameliorate their social determinants of health, including cultural and linguistic competence on behalf of service providers, are urgently needed. Conclusions: Recommendations include networking, collaboration, financial support and active offer of services in both official languages to improve mental health and addictions services through a continuum of care. Systems navigators may facilitate promotion and referral to such services for official language minorities. Résumé Objectifs: La prévalence croissante de la consommation des substances et des dépendances au Canada, tel qu’illustrée par la crise actuelle des opioïdes et exacerbée par la pandémie de la COVID-19, exhorte à l’investigation de populations qui pourraient être particulièrement vulnérables à la consommation problématique de substances. Au Canada, les communautés de langue officielle en situation de minorité (CLOSM), une population à la fois peu étudiée et peu desservie, pourrait bien représenter une telle population. Méthodes: Au moyen de sa stratégie tripartite, employant les méthodologies d’étude de la portée, d’entrevues, et de scan environnemental, cette étude brosse un premier portrait de la réalité actuelle quant à la consommation de substances, aux dépendances et aux services qui y sont voués, parmi les CLOSM au Canada. Résultats: Les résultats révèlent une lacune importante aux niveaux des connaissances et des services desservant les CLOSM dans la majorité des provinces et territoires. Bien que l’état des lieux soit parcellaire en raison du manque d’études scientifiques sur la question, le portrait actuel suffit pour constater que les besoins des CLOSM différent de ceux de leurs pairs de langue majoritaire. Une amélioration des déterminants sociaux de la santé, tel la compétence culturelle et linguistique de la part des pourvoyeurs des services, représente un besoin pressant. Conclusions: Les recommandations, qui comprennent le réseautage, la collaboration, l’appui financier et l’offre active des services dans les deux langues officielles, visent à améliorer les services voués à la santé mentale et aux dépendances auprès des CLOSM au sein d’un continuum de soins. Les navigateurs.rices de systèmes pourraient faciliter l’aiguillage de membres des CLOSM vers ces services.

Des nôtres : une analyse des besoins des personnes LGBTQ2S d’expression française du Manitoba - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya (Collectif LGBTQ du Manitoba et Université de Saint-Boniface, 2021)
Cette étude, menée sous l’impulsion du Collectif LGBTQ* du Manitoba, est la première à sonder les besoins de la communauté LGBTQ2S d’expression française au Manitoba (désormais la « Communauté »). L’objectif était de brosser le portrait de la situation actuelle de ses membres de 18 ans et plus quant à 1) leur profil sociodémographique et ethnoculturel; 2) leurs besoins en matière de soutiens sociaux et de soins de santé; 3) leurs perceptions de discrimination ou de stigmatisation, tant par rapport à la langue qu’à l’orientation sexuelle et/ou à l’identité de genre; et 4) leurs priorités pour l’avenir. Par l’entremise d’un sondage en ligne, la Communauté a su nous informer de ses besoins prioritaires, particulièrement en matière de santé mentale et de soutien social.

Living in a liminal space: Experiences of 2SLGBTQ + official language minority Canadians during the COVID-19 pandemic - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya; Hardy, Stephan; Avanthay-Strus, Jacqueline (Culture, Health & Sexuality, 2023)
The intersecting identities of those identifying with multiple minorities, such as 2SLGBTQ + and ethnolinguistic minorities, bring individuals to have unique experiences, especially concerning health and wellness. This topic is particularly poorly understood among French-speaking official language minority 2SLGBTQ + populations in Canada. Hence, this study was conducted to generate insights into their needs and experiences, through the lens of intersectionality. This quantitative community-based study, a first of its kind in Western Canada, describes the sociodemographic profile, experiences of discrimination and stigmatisation, and needs and challenges pertaining to mental health and social supports of this double minority group. Data were obtained by an online survey conducted in the Canadian province of Manitoba in June 2020. The participant sample was largely homogenous: most were under the age of 55 years, white, educated, and from urban areas. Many reported experiencing dual marginalisation, feeling unaccepted by both of their minority communities (Francophone and 2SLGBTQ+). A sense of isolation, as well as a lack of social connectedness and psychological support, were often reported. Social initiatives and mental health support within environments proactively affirming of the official language of the minority and inclusive of diverse 2SLGBTQ + identities are needed.

The impact of language on emergency department visits, hospitalizations, and lenght of stay among home care recipients - Reaume, M.; Batista, Ricardo; Rhodes, Emily; Knight, Braden; Imsirovic, Haris; Seale, Emily; Riad, Karine; Prud'homme, Denis; Tanuseputro, Peter (Medical care, 2021)
Background: Research considering the impact of language on health care utilization is limited. We conducted a population-based study to: (1) investigate the association between residents’ preferred language and hospital-based health care utilization; and (2) determine whether this association is modified by dementia, a condition which can exacerbate communication barriers. Methods: We used administrative databases to establish a retrospective cohort study of home care recipients (2015–2017) in Ontario, Canada, where the predominant language is English. Residents’ preferred language (obtained from in-person home care assessments) was coded as English (Anglophones), French (Francophones), or other (Allophones). Diagnoses of dementia were ascertained with a previously validated algorithm. We identified all emergency department (ED) visits and hospitalizations within 1 year. Results: Compared with Anglophones, Allophones had lower annual rates of ED visits (1.3 vs. 1.8; P<0.01) and hospitalizations (0.6 vs. 0.7; P<0.01), while Francophones had longer hospital stays (9.1 vs. 7.6 d per admission; P<0.01). After adjusting for potential confounders, Francophones and Allophones were less likely to visit the ED or be hospitalized than Anglophones. We found evidence of synergism between language and dementia; the average length of stay for Francophones with dementia was 25% (95% confidence interval: 1.10–1.39) longer when compared with Anglophones without dementia. Conclusions: Residents whose preferred language was not English were less frequent users of hospital-based health care services, a finding that is likely attributable to cultural factors. Francophones with dementia experienced the longest stays in hospital. This may be related to the geographic distribution of Francophones (predominantly in rural areas) or to suboptimal patient-provider communication.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

Qualité et sécurité des services de santé offerts en situation linguistique minoritaire en Ontario : investigations des données administratives de santé. - Reaume, Michael; Batista, Ricardo; Prud’homme, Denis; Tanuseputro, Peter (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons une synthèse de plusieurs analyses récentes réalisées par notre groupe de recherche à partir de données administratives de santé pour mesurer la qualité et la sécurité des services de santé offerts aux francophones et allophones en Ontario, Canada. Les résultats de nos analyses démontrent que les Ontariennes et les Ontariens qui reçoivent des soins dans leur principale langue d’usage ont généralement de meilleurs résultats cliniques comparés à ceux qui reçoivent des soins dans une langue autre que leur principale langue d’usage. Ceci suggère que la qualité et la sécurité des soins offerts aux patients et aux patientes en situation de discordance linguistique pourraient être améliorées par le pairage de professionnel-patient parlant la même langue, par exemple, en référant un patient à un médecin qui parle la langue du patient, ou en s’assurant que les francophones ont accès aux services en français en milieux désignés en Ontario en vertu de la Loi sur les services en français et que les allophones puissent bénéficier de davantage de services d’interprétariat. Mots-clés : allophones, données administratives de santé, francophones, minorités de langue officielle, minorités linguistiques, qualité et sécurité des soins de santé

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.

In-hospital patient harm across linguistic groups: A retrospective cohort study of home care recipients - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Guerin, Eva; Rhodes, Emily; Carson, Sarah; Prud'homme, Denis; Tanuseputro, Peter (Journal of patient safety, 2022)
Objective Research examining the impact of language barriers on patient safety is limited. We conducted a population-based study to determine whether patients whose primary language is not English are more likely to experience harm when admitted to hospitals in Ontario, Canada. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2010 to 2015) who were subsequently admitted to hospital. Patient language (obtained from home care assessments) was coded as English, French, or other. Harmful events were identified using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results We included 190,724 patients (156,186 Anglophones, 5,110 Francophones, and 29,428 Allophones). There was no significant difference in the unadjusted risk of harm for Francophones compared with Anglophones (relative risk [RR], 0.94; 95% confidence interval [CI], 0.87–1.02). However, Allophones were more likely to experience harm when compared with Anglophones (RR, 1.14; 95% CI, 1.10–1.18). The risk of harm was even greater for Allophones with low English proficiency (RR, 1.18; 95% CI, 1.13–1.24). After adjusting for potential confounders, Anglophones and Allophones were equally likely to experience harm of any type, but Allophones more likely to experience harm from infections and procedures. Conclusions Patients whose primary language was not English or French were more likely to experience harm after admission to hospital, especially if they had low English proficiency. For these patients, the risk of harm from infections and procedures persisted in the adjusted analysis, but the overall risk of harm did not.

The impact of hospital language on the rate of in-hospital harm. A retrospective cohort study of home care recipients in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Rhodes, Emily; Guerin, Eva; Carson, Sarah; Prud’homme, Denis; Tanuseputro, Peter (BMC Health Services Research, 2020)
Background Patients who live in minority language situations are generally more likely to experience poor health outcomes, including harmful events. The delivery of healthcare services in a language-concordant environment has been shown to mitigate the risk of poor health outcomes related to chronic disease management in primary care. However, data assessing the impact of language-concordance on the risk of in-hospital harm are lacking. We conducted a population-based study to determine whether admission to a language-discordant hospital is a risk factor for in-hospital harm. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2007 to 2015) who were admitted to a hospital in Eastern or North-Eastern Ontario, Canada. Patient language (obtained from home care assessments) was coded as English (Anglophone group), French (Francophone group), or other (Allophone group); hospital language (English or bilingual) was obtained using language designation status according to the French Language Services Act. We identified in-hospital harmful events using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results The proportion of hospitalizations with at least 1 harmful event was greater for Allophones (7.63%) than for Anglophones (6.29%, p <  0.001) and Francophones (6.15%, p <  0.001). Overall, Allophones admitted to hospitals required by law to provide services in both French and English (bilingual hospitals) had the highest rate of harm (9.16%), while Francophones admitted to these same hospitals had the lowest rate of harm (5.93%). In the unadjusted analysis, Francophones were less likely to experience harm in bilingual hospitals than in hospitals that were not required by law to provide services in French (English-speaking hospitals) (RR = 0.88, p = 0.048); the opposite was true for Anglophones and Allophones, who were more likely to experience harm in bilingual hospitals (RR = 1.17, p <  0.001 and RR = 1.41, p <  0.001, respectively). The risk of harm was not significant in the adjusted analysis. Conclusions Home care recipients residing in Eastern and North-Eastern Ontario were more likely to experience harm in language-discordant hospitals, but the risk of harm did not persist after adjusting for confounding variables.

Patient-Physician Language Concordance and Cardiovascular Outcomes Among Patients With Hypertension. - Reaume, Michael; Labossière, Mathieu N.; Batista, Ricardo; Van Haute, Stephanie; Tangri, Navdeep; Rigatto, Claudio; Bohm, Clara; Prud’homme, Denis; Tanuseputro, Peter; Lix, L. M. (JAMA Network Open, 2025)
Importance Patients who live in minority language communities often receive health care services of lower quality and safety compared with patients who speak the majority language. Yet the outcomes associated with care provided by physicians who speak a patient’s primary language remain unknown. Objective To examine patient-physician language concordance and the risk of major adverse cardiovascular events (MACEs) among patients with hypertension. Design, Setting, and Participants This retrospective cohort study identified adults with self-reported hypertension in the Canadian Community Health Survey, a national survey that collects data from a representative sample of Canadians, from January 1, 2003, to December 31, 2014. Respondents (excluding those living in Quebec) had their hospitalization and mortality records linked to their survey responses. Data were analyzed from October 2023 to May 2024. Exposures Respondents’ primary home language was defined using language spoken most often at home. Language spoken with a regular physician was used to measure patient-physician language concordance. Respondents who spoke to their regular physician in their primary home language were classified as having received language-concordant care, while all other respondents were classified as having received language-discordant care.

The impact of patient-facility language discordance on potentially inappropriate prescribing of antipsychotics in long-term care home in Ontario, Canada: A retrospective population health cohort study - Reaume, Michael; Peixoto, Cayden; Pugliese, Michael; Tanuseputro, Peter; Batista, Ricardo; Kendall, Claire. E.; Landry, Josette-Renée; Prud’homme, Denis; Chomienne, Marie-Hélène; Farrell, Barbara; Bjerre, Lise M. (BMC Geriatrics, 2024)
Background Appropriate use of medication is a key indicator of the quality of care provided in long-term care (LTC). The objective of this study was to determine whether resident-facility language concordance/discordance is associated with the odds of potentially inappropriate prescribing of antipsychotics (PIP-AP) in LTC. Methods We conducted a population-based, retrospective cohort study of LTC residents in Ontario, Canada from 2010 to 2019. We obtained resident language from standardized resident assessments, and derived facility language by determining the proportion of residents belonging to each linguistic group within individual LTC homes. Using linked administrative databases, we identified all instances of PIP-AP during a 1-year follow-up period. PIP-AP was defined using the STOPP-START criteria, which have previously been shown to predict adverse clinical events such as emergency department (ED) visits and hospitalizations. The association between linguistic factors and PIP-AP was assessed using adjusted multivariable logistic regression analysis. Results We identified 198,729 LTC residents consisting of 162,814 Anglophones (81.9%), 6,230 Francophones (3.1%), and 29,685 Allophones (14.9%). The odds of PIP-AP of were higher for both Francophones (aOR 1.15, 95% CI 1.08–1.23) and Allophones (aOR 1.11, 95% CI 1.08–1.15) when compared to Anglophones. When compared to English LTC homes, French LTC homes had greater odds of PIP-AP (aOR 1.12, 95% CI 1.05–1.20), while Allophone homes had lower odds of PIP-AP (aOR 0.82, 95% CI 0.77–0.86). Residents living in language-discordant LTC homes had higher odds of PIP-AP when compared to LTC residents living in language-concordant LTC homes (aOR 1.07, 95% CI 1.04–1.10). Conclusion This study identified linguistic factors related to the odds of PIP-AP in LTC, suggesting that the linguistic environment may have an impact on the quality of care provided to residents.

La population francophone au sein de votre équipe Santé Ontario : proposition d’indicateurs clés - Réseau des services de santé en français de l'Est de l'Ontario (2022)

Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire - Réseau des services de santé en français de l’Est de l’Ontario (2020)

Rapport provincial sur les SSEF (données de 2018-2019) - Réseau des services de santé en français de l'Est de l'Ontario; Institut Ozi (2020)
Le projet OZi a pour objectif de colliger et d’analyser des données afin de dresser un portrait de la capacité de SSEF. Cette initiative cherche à pallier le manque de données normalisées afin de permettre une planification efficace et une prise des décisions éclairée. Grâce au portail OZi, les fournisseurs de services de santé (FSS) financés par les RLISS ont fourni des données de référence sur leur capacité en matière de SSEF. Le présent rapport porte sur la deuxième année de collecte de données (année 2018-2019). L’analyse porte sur quatre perspectives : la répartition des FSS, le continuum des services, la conformité en matière de désignation et les ressources humaines.

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

État des lieux pour le secteur des soins à domicile et en milieu communautiare dans le nord de l'Ontario - Réseau du mieux-être francophone du Nord de l'Ontario (2025)
Le Réseau a entrepris le travail de recenser les capacités actuelles du secteur des soins à domicile et en milieu communautaire dans le Nord de l’Ontario, et ce, afin de mieux appuyer les organismes de soins de santé et ainsi renforcer les capacités du secteur. En effet, cette étude permettra au Réseau de connaître les capacités actuelles en termes de professionnels de la santé qui parlent le français dans le Nord de l’Ontario, puis d’identifier les domaines et les régions où les disparités sont plus importantes. Ce rapport pourra servir de guide envers l’établissement des priorités et de stratégies régionales en matière de services en français pour le secteur des soins à domicile et en milieu communautaire.

Recommandations de l’étude de besoins sur les foyers de soins de longue durée du Nord de l’Ontario - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Recommendations from the Northern Ontario Long-Term Care Homes Needs Study - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Argumentaire pour la promotion d’une offre de service santé de qualité dans la langue maternelle des clients au Nunavut - Réseau Santé en français au Nunavut (2021)

Pour un accueil en santé des personnes immigrantes francophones au Nunavut - état de situation - Réseau Santé en français au Nunavut (2021)

À la rencontre des communautés acadiennes et francophones et de leurs enjeux en santé - Réseau Santé Nouvelle Écosse (Réseau santé en français de Nouvelle-Écosse, 2021)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

The impact of dementia and language on hospitalizations: A retrospective cohort of long-term care residents - Riad, Karine; Webber, Colleen; Batista, Ricardo; Reaume, Michael; Rhodes, Emily; Knight, Braden; Prud’homme, Denis; Tanuseputro, Peter (BMC Geriatrics, 2020)
Background Hospitalizations carry considerable risks for frail, elderly patients; this is especially true for patients with dementia, who are more likely to experience delirium, falls, functional decline, iatrogenic complications, and infections when compared to their peers without dementia. Since up to two thirds of patients in long-term care (LTC) facilities have dementia, there is interest in identifying factors associated with transitions from LTC facilities to hospitals. The purpose of this study was to investigate the association between dementia status and incidence of hospitalization among residents in LTC facilities in Ontario, Canada, and to determine whether this association is modified by linguistic factors. Methods We used linked administrative databases to establish a prevalent cohort of 81,188 residents in 628 LTC facilities from April 1st 2014 to March 31, 2017. Diagnoses of dementia were identified with a previously validated algorithm; all other patient characteristics were obtained from in-person assessments. Residents’ primary language was coded as English or French; facility language (English or French) was determined using language designation status according to the French Language Services Act. We identified all hospitalizations within 3 months of the first assessment performed after April 1st 2014. We performed multivariate logistic regression analyses to determine the impact of dementia and resident language on the incidence of hospitalization; we also considered interactions between dementia and both resident language and resident-facility language discordance. Results The odds of hospitalization were 39% lower for residents with dementia compared to residents without dementia (OR 0.61, 95% CI 0.57–0.65). Francophones had lower odds of hospitalization than Anglophones, but this difference was not statistically significant (OR 0.91, 95% CI 0.81–1.03). However, Francophones without dementia were significantly less likely to be hospitalized compared to Anglophones without dementia (OR 0.71, 95% CI 0.53–0.94). Resident-facility language discordance did not significantly affect hospitalizations. Conclusions Residents in LTC facilities were generally less likely to be hospitalized if they had dementia, or if their primary language was French and they did not have dementia. These findings could be explained by differences in end-of-life care goals; however, they could also be the result of poor patient-provider communication.

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Centre de recherche en santé dans les milieux ruraux et du nord, 2020)

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal, 2020)

Guide de navigation du réseau de la santé et des services sociaux du Manitoba - Santé en français (2024)

5 enjeux prioritaires en santé des communautés acadienne et francophones - Santé Nouvelle-Écosse; Réseau Santé Nouvelle-Écosse (2022)

Données sur les soins de longue durée en français-Équipe Santé Ontario du Grand Fleuve - Santé Ontario; Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada (2022)

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange Van; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.

Implementing Active Offer of Services in Both Official Languages in a Hospital Setting in Ontario - Sauvé-Schenk, Katrine; Savard, Jacinthe; Durand, François (Healthcare Policy, 2024)
Providing services in a patient's preferred language is linked to safe and quality care. This paper presents the process and outcomes of implementing practices of active offer (AO) of French-language services in a hospital setting in a region of Ontario with a low density of francophones. Participating unit managers and site coordinators selected AO practices and carried out an implementation plan. The implementation's success was linked to the support received from higher management and site coordinators. Challenges included the managers' rival priorities and perceived language priorities. This process could be applied to meet the needs of other language communities.

Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français - Sauvé-Schenk, Katrine; Savard, Jacinthe; Prud’homme, Denis; Durand (Chiocchio), F.; Delluc, C. (Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Vers de nouvelles approches en santé mentale : possibilités et limites pour les francophones en situation minoritaire à Terre-Neuve-et-Labrador et aux Territoires du Nord-Ouest - Savard, Sébastien; van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Oukouami D, Ghisleine; Michel, Jean Nephetaly (Canadian Social Work Review / Revue canadienne de service social, 2024)
De nouvelles approches axées sur la cybersanté mentale l’aide à la navigation du système, les cliniques sans rendez-vous, ainsi que les approches plus traditionnelles comme les lignes d’aide et de crise cohabitent afin de promouvoir ou d’intervenir précocement en santé mentale. Comment ces interventions répondent-elles aux besoins des francophones en contexte linguistique minoritaire alors que la communication est au coeur d’une consultation réussie? Objectif : Documenter six initiatives à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest. Méthode : Études de cas, incluant trente-six entrevues semi-dirigées auprès des autorités sanitaires, des fournisseurs de soins et des usagers. Résultats : La gratuité, l’anonymat, la rapidité, la présence des pairs travailleurs, l’absence de jugement et des démarches simples facilitent l’accès aux programmes. Parmi les limites, l’insuffisance de services en français et l’accent sur les thérapies brèves peuvent affecter la continuité des services, notamment pour les usagers francophones. Conclusion : Malgré les efforts pour améliorer l’offre de services en santé mentale aux francophones, des lacunes subsistent. L’article présente certaines stratégies qui permettraient d’améliorer l’offre de ces services. Mots-clés : Santé mentale, cybersanté mentale, initiatives novatrices, Terre-Neuve-et-Labrador, Territoires du Nord-Ouest, soins par paliers, francophones en situation minoritaire

Reconnaissance du travail des proches aidantes en contexte francophone minoritaire : l'expérience des Fransaskoises - Savoie, Elda; Corriveau, Hélène; Lanteigne, Isabel; Savoie, Lise; Albert, Hélène (Reflets, 2022)
Cet article présente une recherche qualitative visant à comprendre l’expérience des proches aidantes francophones en Saskatchewan, en Alberta et en Colombie-Britannique. Il s’agit d’une recherche qualitative réalisée grâce à une collaboration entre la Fédération provinciale des Fransaskoises et une équipe de chercheures de l’École de travail social de l’Université de Moncton au NouveauBrunswick. L’objectif principal de cette étude était de mettre en lumière les défis rencontrés au quotidien ainsi que les pistes de solutions afin d’améliorer le soutien apporté aux proches aidantes. L’article se concentre sur 31 entretiens individuels réalisés en Saskatchewan. Les résultats de ces entretiens démontrent l’ampleur des conséquences du rôle de la proche aidante sur la santé mentale et physique ainsi que ses conséquences financières. De plus, une analyse selon les régions habitées (rurales ou urbaines) sera présentée pour mettre en lumière, entre autres, les défis rencontrés et les conséquences engendrées par le rôle de proche aidante. Mots-clés : Proche aidante, francophone, région rurale, région urbaine, contexte linguistique minoritaire, conséquence financière, absence de ressources

Recruiting service providers with French proficiency: Tips and strategies - Schutte, Valerie; Erbach, Madison; Summers, Nikky; Jennings, Melissa (The Knowledge Institute on Child and Youth Mental Health and Addictions, 2023)

Contributions d’OZi à l’état des lieux des services de santé en français en Ontario. - Scullion, David; Taillon, Myriam; Ranger, Marie-Christine; Glaude, Normand; Desaulniers, Jacinthe (Minorités linguistiques et société, 2024)
Entre 2017 et 2020, l’organisme OZi a effectué la collecte et l’analyse de données sur les services de santé en français à l’échelle de la province, dans le cadre de la Loi sur les services en français de l’Ontario. Les résultats de cette recherche descriptive et exploratoire portent sur la répartition géographique de l’offre des services de santé en français, le continuum de soins, les exigences de la désignation et les ressources humaines possédant des capacités linguistiques en français. Ces résultats permettent de dresser l’état des lieux des services de santé en français en Ontario, en mettant en lumière les points forts comme les lacunes des services de santé en français. Les résultats sont discutés sous l’angle de l’accès et la planification des services de santé en français ainsi que celui de la performance de la désignation. Mots-clés : santé, offre active, Ontario, désignation des fournisseurs de santé, continuum de soins

Patient-physician language concordance and quality and safety outcomes among frail home care recipients admitted to hospital in Ontario, Canada - Seale, Emily; Reaume, Michael; Batista, Ricardo; Eddeen, Anan. Bader; Roberts, Rihannon; Rhodes, Emily; McIsaac, Daniel. I.; Kendall, Claire. E.; Sood, Manish. M.; Prud'homme, Denis; Tanuseputro, Peter (Canadian Medical Association Journal, 2022)
Background: When patients and physicians speak the same language, it may improve the quality and safety of care delivered. We sought to determine whether patient–physician language concordance is associated with in-hospital and postdischarge outcomes among home care recipients who were admitted to hospital. Methods: We conducted a population-based study of a retrospective cohort of 189 690 home care recipients who were admitted to hospital in Ontario, Canada, between 2010 and 2018. We defined patient language (obtained from home care assessments) as English (Anglophone), French (Francophone) or other (allophone). We obtained physician language from the College of Physicians and Surgeons of Ontario. We defined hospital admissions as language concordant when patients received more than 50% of their care from physicians who spoke the patients’ primary language. We identified in-hospital (adverse events, length of stay, death) and post-discharge outcomes (emergency department visits, readmissions, death within 30 days of discharge). We used regression analyses to estimate the adjusted rate of mean and the adjusted odds ratio (OR) of each outcome, stratified by patient language, to assess the impact of language-concordant care within each linguistic group. Results: Allophone patients who received language-concordant care had lower risk of adverse events (adjusted OR 0.25, 95% confidence interval [CI] 0.15–0.43) and in-hospital death (adjusted OR 0.44, 95% CI 0.29–0.66), as well as shorter stays in hospital (adjusted rate of mean 0.74, 95% CI 0.66–0.83) than allophone patients who received language-discordant care. Results were similar for Francophone patients, although the magnitude of the effect was smaller than for allophone patients. Language concordance or discordance of the hospital admission was not associated with significant differences in postdischarge outcomes.

Culture de sécurité des professionnels de santé en soins primaires : adapatation en langue française du questionnaire MOSPSC (« Medical Office Survey on Patient Safety Culture ») - Shih, C.; Buchet-Poyau, K.; Keriel-Gascou, M.; Quenon, J.-L.; Michel, P.; Touzet, S.; Chanalière, Marc (Revue d'Épidémiologie et de Santé Publique, 2022)
Contexte La culture de sécurité (CDS) rend compte de déterminants individuels et organisationnels. Son évaluation auprès des professionnels de santé en soins primaires (SP) peut être réalisée par des questionnaires auto-administrés, tel le « Medical Office Survey on Patient Safety Culture » (MOSPSC). Objectif Adapter en français le questionnaire MOSPSC et en étudier les propriétés psychométriques. Méthode Le questionnaire MOSPSC a fait l'objet d'une traduction avec analyse linguistique en langue française ; une rétrotraduction vers l'anglais a été réalisée, conformément aux recommandations de l'ISPOR. La version française du questionnaire a été diffusée à 415 professionnels de santé de 36 structures pluriprofessionnelles ambulatoires. L’étude des propriétés psychométriques (test-retest, α de Cronbach et analyse factorielle) a été conduite à partir des réponses des professionnels. Résultats Après analyse linguistique, la notion d’équipe a été traduite par celle de structure dans le questionnaire final. Le taux de participation des professionnels à l'enquête était de 64,1 % (266/415) ; 51,9 % (138/415) étaient des paramédicaux (principalement IDE ou kinésithérapeutes). Le coefficient α de Cronbach est de 0,94 pour l'ensemble des dimensions. Après analyse psychométrique, la dimension « signalement des évènements indésirables » a été ajoutée, et celle de « formation du personnel » intégrée à celle de « formation et standardisation des pratiques », portant à 13 le nombre de dimensions identifiées après analyse factorielle. Conclusion Le questionnaire MOSPSC adapté et validé en français peut être utilisé pour mesurer la CDS des professionnels en soins primaires en France. Son usage permettrait d'envisager à terme des comparaisons à l’échelle de chaque structure, pour y suivre l’évolution de la CDS, et dans le cadre de recherches nationales et internationales sur la gestion des risques en soins primaires.

Le renforcement des capacités : déclin ou levier à l'amélioration de la qualité de vie des aînés ? Le cas de St-Wilfred et de Robertville en Acadie - Simard, Majella (Reflets, 2022)
Le vieillissement de la population représente une réalité complexe. Bien que les causes attribuables à ce phénomène fassent consensus auprès des chercheurs, ses manifestations et ses conséquences diffèrent d’un endroit à l’autre. Dès lors, le rythme et l’intensité du vieillissement ainsi que les moyens déployés par les différents acteurs sociaux pour en atténuer les effets et améliorer les conditions de vie des aînés se manifestent aussi différemment selon les milieux géographiques. Pour diverses raisons liées à la démographie et à la géographie, les défis liés à la gestion du vieillissement tendent à se manifester avec plus d’acuité en milieu minoritaire francophone. L’objectif de cet article consiste à examiner la contribution du modèle de renforcement des capacités à l’amélioration de la qualité de vie des aînés vivant au sein de deux localités sises en milieu rural minoritaire francophone. L’étude de cas exploratoire couplée à l’approche des représentations sociales des acteurs a été retenue comme méthode d’analyse. Des entrevues semi-dirigées effectuées auprès d’intervenants locaux et communautaires ainsi que la tenue de deux groupes de discussion constituent les instruments d’analyse qui ont été mobilisés. Bien que les résultats de notre analyse révèlent le rôle d’avant-plan de la résilience, du réseautage, de la vie relationnelle, du sentiment identitaire et du capital social dans l’amélioration de la qualité de vie des aînés, ces composantes relatives à leurs facultés s’avéreraient insuffisantes afin de favoriser un vieillissement sur place, d’où la nécessité de déployer en amont une politique territoriale du vieillissement. Mots-clés : vieillissement, milieu rural, renforcement des capacités, qualité de vie, Acadie

Inégalités sociales et enjeux liés à la santé des aînés francophones en situation minoritaire : le cas de l’Atlantique et de l’Acadie des Maritimes - Simard, Majella; Bouchard, Louise (Organisations & Territoires, 2020)
Le vieillissement démographique soulève des enjeux fondamentaux dans la réponse des acteurs sociaux aux besoins manifestés par les aînés sur le plan de la santé. L’objectif de cette contribution est double. Il consiste, d’une part, à identifier les principaux enjeux auxquels sont confrontés les aînés francophones en situation minoritaire sur le plan de la santé et, d’autre part, à examiner la situation des inégalités sociales et les conditions de vie qui en découlent comme déterminant de la santé, de la qualité et de l’accès aux services dans une perspective de développement territorial. Les résultats de notre analyse révèlent que le rapport minoritaire/ majoritaire traduit une inégalité sociale qui, couplée à d’autres déterminants sociaux, contribue de facto à la formation de disparités sur le plan de la santé, d’où la nécessité de mettre en oeuvre une politique à l’endroit des aînés vivant en milieu minoritaire francophone destinée à réduire de tels écarts.

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)

Enjeux et complexité de la démence en milieu rural francophone : regards sur les réalités familiales [mémoire de maîtrise, Université d'Ottawa] - Sullivan, Cassidy (Université d'Ottawa, 2020)
Les personnes aînées se retrouvent parmi les groupes les plus susceptibles d’être diagnostiqués d’une maladie cognitive, telle qu’une démence. La réception du diagnostic est un événement bouleversant pour toutes les personnes impliquées, et plus particulièrement pour les familles. Dans la région d’Ottawa, il existe une variété de ressources pour soutenir les personnes atteintes d’une démence ainsi que leurs proches. Or, la littérature disponible indique que les personnes francophones vivant dans un milieu rural ne vivent pas la même réalité (Forgues, Doucet et Guignard (2011). Bien que les impacts de la démence sur les relations familiales pourraient varier d’un endroit à un autre, l’emplacement et la disponibilité des services francophones jouent également un rôle important dans le parcours de ces personnes. Ces facteurs nous invitent à poser la question suivante : Quels sont les impacts de la démence sur la dynamique familiale et l’accès aux services francophones des personnes vivant dans un milieu rural ? À partir de la perspective d’intervenantes sociales, l’étude a permis : 1) d’explorer les réalités et enjeux vécus par les familles lors de la réception d’un diagnostic de démence, comme la maladie d’Alzheimer, chez un proche âgé vivant dans un contexte rural francophone ; 2) d’examiner les défis d’accès aux services rencontrés par les aidants familiaux, et finalement ; 3) de comprendre les réalités des familles lors de la progression de la maladie. Cette recherche a été menée dans les Comtés unis de Prescott-Russell, une région bilingue de l’est de l’Ontario. Dans cette étude, nous avons identifiés le vécu des familles suite à la réception d’un diagnostic de démence, ainsi que les ressources disponibles pour les personnes de cette région qui sont touchées par la maladie. En ce qui trait au cadre conceptuelle et théorique choisi pour cette étude, nous avons optés pour l’épreuve relationnelle et l’approche écosystémique pour analyser nos thèmes. Sur le plan méthodologique et en se basant sur des entrevues semi-dirigées, cette étude a nécessité la participation de trois intervenantes sociales œuvrant auprès des familles ayant un proche atteint d’une démence, et ce, dans la région de Prescott-Russell. Il ressort principalement des résultats de cette étude que les enjeux observés par les intervenantes sur la gestion de la démence en milieu rural et l’accès aux services sont lié à la navigation entre les services, l’éducation sur la démence et l’optimisation des services de soutien. Ces dernières constatent des points à améliorer en ce qui concerne le discours social sur le vieillissement ainsi que le manque de financement pour l’augmentation de la visibilité et de l’accessibilité des services francophones. Mots clés : Personne aînée, maladie d’Alzheimer, ruralité, francophonie, accessibilité, services adaptés, dynamique familiale

Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. - Thifault, Marie-Claude (Le moment Monfort dans la francophonie canadienne, 2024)

Dérives : une histoire sensible des parcours psychiatriques en Ontario français - Thifault, Marie-Claude; LeBel, Marie (Les Presses de l'Université d'Ottawa, 2021)

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Improving access to health services in French: The power of networking and knowledge mobilization, a proven Canadian Model - Tremblay, Michel; Leis, Anne (Linguistic Minorities and Society, 2021)
Language barriers have a detrimental impact on access to health services and compromise patients’ safety. The purpose of this article is to describe and evaluate how the Société Santé en français (SSF) and the 16 French Language Health (FLH) networks used networking and knowledge mobilization for improving access to health services in French for Francophone and Acadian minority communities (FAMC). Method: Data was extracted from the 2013-2018 program’s reports and evaluation. Results confirmed that networking effectively mobilized key partners for better access to health services in French regardless of location. This access increased incrementally as a function of the customized level of support provided to the system by the SSF and the FLH networks and, to a lesser extent, when FAMC represented over 3.5% of the total population in the region, province or territory. Networking and knowledge mobilization contribute to augmenting access to safe, quality health services in French for FAMC. Keywords: access, partnership and networking, active offer, language barriers, knowledge mobilization

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Research Component. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon. Executive summary - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Volet Recherche. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.

Pratique # 25 : Accès éQUITÉ : Simplifier l’accès aux services de santé en français (Société Santé en français) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratique # 26 : Accès santé jeunesse Péninsule acadienne (ASJPA) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

La santé mentale en contexte francophone minoritaire : état des connaissances - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe (Minorités linguistiques et société, 2024)
Contexte : La communication est une composante essentielle de la relation thérapeutique qui peut être entravée lorsque la culture et la langue de la personne intervenante et du patient diffèrent. En contexte francophone minoritaire, ces problèmes se posent avec acuité dans le domaine de la santé mentale. Objectif : Rendre compte des travaux de recherche effectués sur le thème de la santé mentale et des communautés francophones en contexte linguistique minoritaire. Méthode : Analyse documentaire de 59 publications couvrant la période de 2000 à 2022. Retombées : La synthèse permet de dégager quatre grands constats : a) le processus de désinstitutionnalisation a été à l’origine de la mise en place de politiques linguistiques en santé mentale; b) les données issues des enquêtes canadiennes n’ont contribué que partiellement à améliorer les connaissances sur les états de santé mentale et leurs déterminants; c) l’association entre l’identité culturelle et linguistique et la santé mentale a été explorée, permettant de mieux comprendre des phénomènes comme l’effet du rapport minorité-majorité et de l’insécurité linguistique sur la santé mentale; d) l’accès à des services de santé mentale dans sa langue demeure toujours un défi pour les francophones en contexte minoritaire. Mots-clés : synthèse de littérature, services et politiques en santé mentale, minorité de langue officielle, minorité francophone, Canada

Pratiques novatrices en santé mentale pour les populations de langue officielle minoritaire à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Savard, Sébastien; Oukouomi, G.; Michel, J. N. (Université d'Ottawa, Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Quand le terrain informe les interventions communautaires. - van Kemenade, Solange; Tremblay, Éléonore; Benhamadi, Bey; Moussard, Aline; Michel, Jean Nephetaly (Minorités linguistiques et société, 2024)
L’Abécédaire d’un cerveau en santé – Sensibilisation à la démence dans l’Ouest et le Nord est un projet chapeauté par RésoSanté Colombie-Britannique et mis en oeuvre en partenariat avec les réseaux de Santé en français de la Saskatchewan, de l’Alberta et du Yukon. Ses objectifs étaient : a) produire des connaissances pour mieux comprendre la problématique de la démence et son impact dans les communautés francophones dans les provinces et le territoire ciblés; b) prévenir la démence et réduire la stigmatisation des personnes atteintes de troubles neurodégénératifs. Cet article se concentre sur le volet recherche du projet qui a accompagné l’intervention communautaire. Des entrevues semi-structurées (N=29) et un sondage en ligne (N=282) auprès des communautés francophones, des personnes proches aidantes, des intervenantes et des intervenants ainsi que du personnel oeuvrant dans les organisations de la francophonie ont été réalisées. L’étude a contribué à documenter la nécessité de services de prévention, de diagnostic, de soutien et de soins en français en matière de troubles neurocognitifs, à repérer des populations plus vulnérables et à recenser des bonnes pratiques. La recherche sur le terrain a éclairé les responsables et les partenaires du projet dans le choix des interventions communautaires appropriées en matière de prévention et de sensibilisation dans un contexte linguistique minoritaire. Mots-clés : troubles cognitifs, démence, francophones en situation minoritaire, interventions communautaires, Canada

Création d'une grille d'observation pour simulations sur l'offre active de services de santé en français - Vincent, Coralie; Bodnaruc, Alexandra Maria; Kengneson, Cris-Carelle; Savard, Jacinthe; Giroux, Isabelle (Reflets, 2021)
Au Canada, il fut démontré que les communautés francophones vivant en situation linguistique minoritaire éprouvent des difficultés à se prévaloir de services sociaux et de santé dans leur langue de préférence, ce qui peut négativement affecter la qualité et la sécurité des services. L’offre active est une pratique visant à contrer les effets de la minorisation linguistique en invitant, de manière proactive et dès le premier contact, les bénéficiaires à s’exprimer dans la langue officielle de leur choix. Il n’existe actuellement aucun outil validé permettant l’évaluation de cette compétence auprès des futurs professionnels des domaines de la santé et des services sociaux. Cet article présente les étapes de création et de validation de Grille d’observation des indicateurs de compétence la en offre active de services en français, laquelle vise à soutenir les programmes de formation dans l’enseignement et l’évaluation de cette compétence au moyen de simulations. Mots-clés : minorités linguistiques, offre active de services en français, langue et services, qualité des soins, formation professionnelle en santé et service social, grille d’observation, validation

Évaluation de la fidélité interjuges d’une grille d’observation des comportements d’offre active de services en français dans le cadre d’activités d’apprentissage par simulation - Vincent, Coralie; Bodnaruc, Alexandra Maria; Savard, Jacinthe; Kengneson, Cris-Carelle; Benoît, Josée; Giroux, Isabelle (Minorités linguistiques et société / Linguistic Minorities and Society, 2023)
Résumé Dans les régions canadiennes où les communautés francophones vivent en situation minoritaire, l’offre active (OA) de services en français consiste à proposer des services en français de façon proactive et dès le premier contact. Dans le contexte des services sociaux et de santé, l’OA contribue à la qualité, à la sécurité et à l’équité des soins destinés à ces communautés. La Grille d’observation des indicateurs de compétence en OA a été créée pour évaluer cette compétence chez les futurs professionnels dans un contexte d’apprentissage par simulation. Le présent projet de recherche visait à poursuivre l’évaluation métrologique de la grille en mesurant sa fidélité interjuges grâce au coefficient de corrélation intraclasse (CCI). Les résultats ont démontré un niveau de fidélité globale élevé (CCI = 0,87), ce qui permet d’encourager l’utilisation de la grille dans les milieux d’apprentissage. Des recherches supplémentaires permettront d’évaluer la fidélité de la grille dans divers contextes et d’assurer l’amélioration continue de la formation des futurs professionnels sur l’OA. Mots-clés : outils d’évaluation, offre active de services en français, formation des professionnels de la santé, apprentissage par simulation, fidélité interjuges Abstract In Canadian Francophone minority communities, the active offer (AO) of French language services involves proactively offering services in French from the first point of contact. In the context of health and social services, the AO contributes to the quality, safety and equity of care within these communities. The AO Competency Indicator Observation Grid was created to assess AO competency among future professionals in a simulated learning environment. The purpose of this research project was to continue the metrological evaluation of the grid by measuring its inter-rater reliability using the intraclass correlation coefficient (ICC). The results demonstrated a high level of global reliability (ICC = 0.87), thus supporting the use of the grid in learning environments. Further research will evaluate the reliability of the grid in a variety of settings and ensure continued improvement in the training of future professionals on the AO. Keywords: assessment tools, active offer of French language services, health professional education, simulated learning, inter-rater reliability

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.